A microfluidic device and automatic counting system for the study of C. elegans reproductive aging. Issue 2 (19th November 2014) - Li, Siran; Stone, Howard A.; Murphy, Coleen T.
Abstract : We report the development of a microfluidic assay and a real-time, automatic progeny counting system that records progeny counting information from many individual C. elegans hermaphrodites. Abstract : The nematode Caenorhabditis elegans ( C. elegans ) is an excellent model to study reproductive aging because of its short life span, its cessation of reproduction in mid-adulthood, and the strong conservation of pathways that regulate longevity. During its lifetime, a wild-type C. elegans hermaphrodite usually lays about 200–300 self-fertilized hatchable eggs, which mainly occurs in the first three to five days of adulthood. Here, we report the development of a microfluidic assay and a real-time, automatic progeny counting system that records progeny counting information from many individual C. elegans hermaphrodites. This system offers many advantages compared to conventional plate assays. The flow of non-proliferating bacteria not only feeds the worms but also flushes the just-hatched young progeny through a filter that separates mothers from their offspring. The progeny that are flushed out of the chamber are detected and recorded using a novel algorithm. In our current design, one device contains as many as 16 individual chambers. Here we show examples of real-time progeny production information from wild-type (N2) and daf -2 (insulin receptor) mutants. We believe that this system has the potential to become a powerful, high time-resolution tool to study the detailed reproduction of C. elegans .